Gestão verde em cadeias de suprimento: estudo nas cadeias de suprimento agroalimentares do arroz e do pêssego - Herrmann, Felipe Fehlberg (Universidade do Vale do Rio dos Sinos, 2018)
This study analyzes the green practices in the agricultural supply chains of rice and peach, and examines their relationships with various categories and dimensions in the context of sustainable supply chain management/supply chains. The main objective of this study is to propose a model to evaluate the effectiveness of the implementation of green practices in agri-food supply chains. Existing theoretical research classifies green practices into 21 categories, which are grouped within three dimensions—strategy, innovation, and operations. Based on a systematic review of the literature, five hypotheses were proposed in this study, three of which associate the dimensions with competitiveness. On the other hand, the remaining two hypotheses take into consideration the relationships of reputation and result with competitiveness. A quantitative survey was conducted on 92 companies involved in the rice and peach supply chains. Factorial analysis was used to evaluate the reliability and validity of the constructs. The hypotheses were tested using structural equation modeling. The results were as follows: (i) no relationship was found between Strategy and Competitiveness; (ii) Innovation was positively associated with Competitiveness; (iii) the Operations dimension was strongly and positively associated with Competitiveness; and (iv) Result and Reputation were strongly and positively associated with Competitiveness. This research contributes to the literature by proposing a model that allows for the evaluation of green practices in rice and peach supply chains. In addition, the study conceptually and empirically examines the relationship between green practices and competitiveness of the (agricultural) supply chain” would read better here.
Keywords: Práticas-verdes; Gestão verde de cadeias de suprimento; Competitividade; Análise fatorial; Modelagem de equações estruturais; Green practices; Green supply chain management; Competitiveness; Factorial analysis; Structural equation modeling; ACCNPQ::Engenharias::Engenharia de Produção